4g+3(-4+4g)=1-g

Simple and best practice solution for 4g+3(-4+4g)=1-g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4g+3(-4+4g)=1-g equation:


Simplifying
4g + 3(-4 + 4g) = 1 + -1g
4g + (-4 * 3 + 4g * 3) = 1 + -1g
4g + (-12 + 12g) = 1 + -1g

Reorder the terms:
-12 + 4g + 12g = 1 + -1g

Combine like terms: 4g + 12g = 16g
-12 + 16g = 1 + -1g

Solving
-12 + 16g = 1 + -1g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add 'g' to each side of the equation.
-12 + 16g + g = 1 + -1g + g

Combine like terms: 16g + g = 17g
-12 + 17g = 1 + -1g + g

Combine like terms: -1g + g = 0
-12 + 17g = 1 + 0
-12 + 17g = 1

Add '12' to each side of the equation.
-12 + 12 + 17g = 1 + 12

Combine like terms: -12 + 12 = 0
0 + 17g = 1 + 12
17g = 1 + 12

Combine like terms: 1 + 12 = 13
17g = 13

Divide each side by '17'.
g = 0.7647058824

Simplifying
g = 0.7647058824

See similar equations:

| 6x+(x+5)=189 | | x^3+2x-2= | | f(x)=-2x^3+5x^2+2x-5 | | 12x^2+16x=3 | | 4(w-5)-2(w+1)=3(1-w) | | X+(2x-75)=90 | | (6-y^5)(6+y^5)= | | -22=3+5u | | 1/2+(2/3/3/4)-(4/5*5/6)= | | -4(4+6b)=80 | | 5z^3-15z^2-1520z=0 | | 2.9=6.9-0.8x | | 3m-3-5=-20 | | 35t=50t-37.5 | | (6xy^2-xy)(6xy^2+xy)= | | 4(y+1)=-6 | | x^2-2x+10=y | | 5x+2x-5=44 | | 7t^3-21t^2-2926t=0 | | 9+5x=4x+12 | | -4+5w=-14 | | 8x+9x-52=104-9x | | -(x-8)=3(-3x+4) | | 8=Xsquared-5x+8 | | 120+30m=80+50m | | 5-x=18+3x | | 4+2.5x=6.5x+2 | | -1+3-x=4+2x | | 28.75=6g+3.97 | | -6(2n-1)=-66 | | a+4+4a=14 | | 2g+16=2g+28 |

Equations solver categories